Message from the Chief Executive Officer - Harley, Catherine (Canadian Journal of Wound, Ostomy and Continence, 2026)
"The Whole is Greater than the Sum of the Parts" - Aristotle A happy new year to you all! I want to thank you all for your contributions. 2025 was another transformative year for Nurses Specialized in Wound, Ostomy and Continence Canada (NSWOCC®). It was a year in which we strengthened our core programs and the Wound, Ostomy and Continence Institute further, growing our organization by welcoming new members and rolling out important initiatives that will help to guarantee our continued success in the future. Working together, we made good progress toward our strategic goals and partnered to launch important educational programs such as the Indigenous ECHO Skin and Wound program. We also completed our first Ontario Ministry of Health and Long-Term Care contract for the education of 90 Skin Wellness Associate Nurses (SWAN (TM)) in Ontario Long-Term Care (LTC) facilities. We have now embarked on our second contract for 150 SWANs(TM) and 600 Personal Support Workers in Ontario LTC facilities. One of our largest initiatives is the upcoming World Council of Enterostomal Therapy (WCET®) joint Congress with NSWOCC® which will take place at the Vancouver Convention Center April 24-28, 2026. Together, our collective passion for making wound, ostomy and continence care the best that it can be, has been the center of our collaboration with WCET®. We truly appreciate this opportunity to bring nurses who have specialized in wound, ostomy and continence together from around the world to share best practice and learn from each other. I want to thank you for your continued commitment and effort. Every one of us has an important role to play in the work ahead and I’m confident that together we will achieve great things. I wish you and your loved ones a happy and successful 2026!